2002
DOI: 10.1183/09031936.02.00068002
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic evaluation of pulmonary hypertension

Abstract: Haemodynamic evaluation of pulmonary hypertension. D. Chemla, V. Castelain, P. Hervé, Y. Lecarpentier, S. Brimioulle. #ERS Journals Ltd 2002. ABSTRACT: Pulmonary hypertension is characterised by the chronic elevation of pulmonary artery pressure (PAP) and pulmonary vascular resistance (PVR) leading to right ventricular enlargement and hypertrophy. Pulmonary hypertension may result from respiratory and cardiac diseases, the most severe forms occurring in thromboembolic and primary pulmonary hypertension.Pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
188
2
26

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(220 citation statements)
references
References 135 publications
(196 reference statements)
4
188
2
26
Order By: Relevance
“…It has been shown that those individuals with the positive criteria at pulmonary vasoreactivity test show lower basal hemodynamic impairment, with vasoconstriction predominating in these patients when compared to the remodeling phenomenon 21,22 . These patients may have sustained hemodynamic and clinical response to the introduction of nonselective vasodilators to pulmonary circulation, with improved prognosis, specifically with calcium channel blockers, which are accessible and affordable drugs 9,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that those individuals with the positive criteria at pulmonary vasoreactivity test show lower basal hemodynamic impairment, with vasoconstriction predominating in these patients when compared to the remodeling phenomenon 21,22 . These patients may have sustained hemodynamic and clinical response to the introduction of nonselective vasodilators to pulmonary circulation, with improved prognosis, specifically with calcium channel blockers, which are accessible and affordable drugs 9,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Mean pulmonary arterial pressure (PAP) was figured out by the formula of 79-(0.45X pulmonary artery acceleration time) (13,14).…”
Section: Echocardiographymentioning
confidence: 99%
“…Common findings in the evaluation of patients with PH include dilatation of the right heart chambers, right ventricular hypertrophy, paradoxical septal movement, and tricuspid insufficiency. (4)(5)(6)(7) According to some studies, (8,9) a large percentage of patients with CF present subclinical PH. The great phenotypic variability of the disease (10) justifies a systematic diagnostic approach to evaluate PH in a population of adolescent and adult patients in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…When the hypoxic state is prolonged, the pulmonary circulation suffers structural alterations collectively known as remodeling, characterized by hypertrophy and hyperplasia of the arterial media, as well as by muscle fibers in the peripheral vessels. (3)(4)(5) The diagnostic procedure that is the most accurate in identifying the onset of PH is heart catheterization, and the most sensitive noninvasive technique for the early detection and monitoring of PH is Doppler echocardiography. (4,5) Echocardiography allows us to identify and quantify PH, as well as to determine its variability and the repercussions for the right heart chambers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation